The Role Of The Vedas In Forming Ethical And Humanistic Personality - I Gede Sugiarka (Eduvest - Journal of Universal Studies, 2025)
The Vedas, as the primary source of Hindu teachings, contain universal values that guide human beings toward ethical and humanistic living. This article aims to examine the role of the Vedas in shaping an ethical and humanistic personality. Using a qualitative descriptive approach, this study analyzes Vedic texts, religious literature, and modern theories of ethics and humanism. The findings reveal that the Vedas emphasize the balance between spirituality and morality through the principles of dharma, satya, ahimsa, and tat tvam asi. These values serve as the foundation for forming individuals who are empathetic, just, and respectful of life. This study highlights that the Vedas not only regulate the relationship between humans and God but also provide an ethical framework for building a dignified and civilized society.